Acoustic Measurements at the Rock Painting of Värikallio, Northern Finland - Rainio, Riitta; Lahelma, Antti; Äikäs, Tiina; Lassfolk, Kai; Okkonen, Jari (2016)
In Northern Finland, by the rock painting of Värikallio (ca. 3000–500 BC), several echoes can be heard. The most remarkable of these appear to be originating from the painted rock itself. The article presents the first results of the research project that seeks to explore the role of sound in the development and use of Finnish rock art and Sámi offering sites. Field recordings, made at the site of Värikallio in summer 2013, are analyzed with a sound analysis and visualization toolkit, and interpreted with the help of GIS data and a 3D model of the site. A probable depiction of a drummer, identified in the painting in the course of the fieldwork, provides a further clue to the significance of sound rituals at rock paintings. Non peer reviewed